Superficial CD34‐positive fibroblastic tumor and PRDM10‐rearranged soft tissue tumor are overlapping entities: a comprehensive study of 20 cases. Issue 5 (5th September 2021) - Perret, Raul; Michal, Michael; Carr, Richard A; Velasco, Valérie; Švajdler, Marian; Karanian, Marie; Meurgey, Alexandra; Paindavoine, Sandrine; Soubeyran, Isabelle; Coindre, Jean‐Michel; Boidot, Romain; Charon‐Barra, Céline; et al.
Abstract : Aims: Superficial CD34‐positive fibroblastic tumor (SCD34FT) and PRDM10 ‐rearranged soft tissue tumor ( PRDM10 ‐STT) are rare mesenchymal tumors. These lesions have clinicopathological similarities, but their relationship remains controversial. This study aimed to characterise a series of cases of SCD34FT and PRDM10 ‐STT. Methods and results: Ten lesions each of SCD34FT and PRDM10 ‐STT were studied using immunohistochemistry, array‐comparative genomic hybridisation (aCGH), RNA sequencing and exome sequencing. Tumors mainly occurred in young adults, were generally small (< 5 cm) and arose predominantly in the superficial soft tissues of the lower extremities. Follow‐up data were available in 15 cases (SCD34FT, n = 7, median 16 months; PRDM10 ‐STT, n = 8, median 14 months), local recurrences occurred in four cases (SCD34FT, two of 10; PRDM10 ‐STT, two of 10), while no distant spread was documented. Morphologically, tumors were relatively well‐circumscribed and composed of sheets and fascicles of spindle and pleomorphic cells showing low mitotic activity (< 1/mm²) without necrosis. Other findings included: granular cell change, lipoblast‐like cells, ectatic blood vessels with fibrinous material, myxoid stromal changes, metaplastic bone and increased mitotic activity (> 1/mm²). All tumors diffusely expressed CD34, while pan‐keratin and desmin were commonly seen focally. SynCAM3 was diffusely expressed in 12 cases (SCD34FT, n = 5; PRDM10 ‐STT, n = 7), independently of fusion status. aCGH profiles were 'flat' ( PRDM10 ‐STT, n = 4; SCD34FT, n = 2) and exome sequencing showed no recurrent pathogenic mutations ( PRDM10 ‐STT, n = 2; SCD34FT, n = 4). Overall, the only morphological features seen exclusively in PRDM10 ‐STT were myxoid stromal changes (three of 10) and metaplastic bone (two of 10). Conclusion: We expand the current knowledge on PRDM10 ‐STT and SCD34FT and provide additional evidence for considering them as overlapping entities. Abstract :